(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: to investigate the clinical characteristics and structures in the nasal cavity affecting on midle meatus drainage in patients with chronic rhinosinusitis. Subjects and methods: cross-sectional description of a clinical case series. Results: Among the 183 patients who came for examination, the highest rate of symptom was runny nose 49,7%, nasal congestion 27.3%, head-face heaviness 21.9%, sneezing 1,1%. The rate of nasal mucosa congestion was highest at 73.4%. The majority of cases having septal deformity were 74,3% and concha bullosa was 43,7%. The rate of opaque mucous membrane in the midle meatus was more than 53,6%. Conclusion: Among the patients participating in the study, the highest rate of runny nose and nasal congestion was noted, and the presence of septal deformities was the majority in the patients.